Стан і перспективи дослідження поетичної мови Тараса Мельничука - Тищенко, Зара Робертівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article clarified the state of study in modern Ukrainian Philology of the poetics works of T. Melnychuk. Few literary studio devoted to the analysis of the place of the writer in the new literature. The writing of literary critics considered the genre-stylistic features of the works, their symbols, characterized by ideological aesthetic dominants in the context of the sixties. The object of modern linguistic research of the poetic language of T. Melnychuk is archetype characters epithets kavooras on the colour symbol, dialect, unusual derivative nouns. There are some studies novotwist. T. Melnychuk in the context of the study of Ukrainian poetry. Outlined promising areas of linguistic study of poetic language T. Melnychuk, in particular stilistika-syntactic organization of the poetic text, as the representative of beastily writer.